Mid-infrared Suspended Waveguide Platform and Building Blocks - Wanguemert-Pérez, Juan Gonzalo; Sánchez-Postigo, Alejandro; Soler-Penades, Jordi; Ortega-Moñux, Alejandro; Nedeljkovic, Milos; Halir, Robert; El Mokhtari Mimun, Faysal; Cheng, Y.X.; Qu, Z; Khokhar, Ali Z.; Osman, A.; Cao, Wei; et al. (My University, 2018)
In this work we present our recent progress in the development of a platform for the mid-infrared wavelength range, based on suspended silicon waveguide with subwavelength metamaterial cladding. The platform has some intrinsic advantages, which make it a very promising candidate for sensing applications in the fingerprint region. Specifically, it can cover the full transparency window of silicon (up to a wavelength of 8 μm), only requires one lithographic etch-step and can be designed for strong light-matter interaction. Design rules, practical aspects of the fabrication process and experimental results of a complete set of elemental building blocks operating at two very different wavelengths, 3.8 μm and 7.67 μm, will be discussed. Propagation losses as low as 0.82 dB/cm at λo=3.8 μm and 3.1 dB/cm at λo=7.67 μm are attained, for the interconnecting waveguides.
Keywords: Óptica integrada; Integrated optics; Subwavelength structures; Mid-infrared; Waveguides; Optical devices